Screening technologies for infrastructure projects for post-war restoration of regions of Ukraine - Borodina, O.; Korytko, T. (Економічний вісник Донбасу, 2025)
The research conducted in the article is devoted to the consideration of screening as a technology for assessing and filtering potential projects for the development of regional infrastructure based on their feasibility, potential for success and compliance with the strategic goals of post-war development of the territory. The close connection between infrastructure development and the transformation of domestic policy in the context of the challenges of wartime and the risks of post-war uncertainty is emphasized. Based on the analysis of the current socio-economic cross-section of territorial development, the need for a differentiated approach to the reconstruction of each community is noted. Transparent mechanisms for attracting and controlling the use of investment funds are identified as a necessary condition for effective post-war development. Screening, as one of the organizational technologies for project management that provide the above requirements, is a relevant and acceptable mechanism for foreign partners. It lies in the plane of the Principles of Quality Infrastructure Investment (QII Principles), adopted in 2019 within the framework of the G20 activities, and ensures project risk management. The analysis of screening as a continuous management mechanism that helps minimize project uncertainty allowed the stakeholders of the infrastructure investment process to be systematized and a case study of screening methods was proposed. The study paid special attention to metrics as indicators of the state of the system in general and indicators of the effectiveness of infrastructure projects, and a combined approach to determining their set in the process of infrastructure design of post-war development was proposed. Based on the research materials, the entire process of conducting a screening assessment of infrastructure projects was systematized with its detailing into stages. It was found that the adaptive program-project approach to community development strategizing, unlike traditional program-target planning, has the characteristics and plays the role of an innovative management technology for territorial development. Дослідження, проведене у статті, присвячене розгляду скринінгу як технології оцінки та фільтрації потенційних проектів розвитку регіональної інфраструктури на основі їхньої доцільності, потенціалу успіху та відповідності стратегічним цілям повоєнного розвитку території. Підкреслюється тісний зв'язок між розвитком інфраструктури та трансформацією внутрішньої політики в контексті викликів воєнного часу та ризиків повоєнної невизначеності. На основі аналізу сучасного соціально-економічного зрізу територіального розвитку зазначається необхідність диференційованого підходу до відбудови кожної громади. Прозорі механізми залучення та контролю використання інвестиційних коштів визначені як необхідна умова ефективного повоєнного розвитку. Скринінг, як одна з організаційних технологій управління проектами, що забезпечує вищезазначені вимоги, є актуальним та прийнятним механізмом для іноземних партнерів. Він лежить у площині Принципів якісного інвестування в інфраструктуру (QII Principles), прийнятих у 2019 році в рамках діяльності G20, та забезпечує управління ризиками проектів. Аналіз скринінгу як механізму безперервного управління, що допомагає мінімізувати невизначеність проектів, дозволив систематизувати зацікавлені сторони процесу інвестування в інфраструктуру та запропонувати тематичне дослідження методів скринінгу. У дослідженні особливу увагу приділено метрикам як індикаторам стану системи загалом та індикаторам ефективності інфраструктурних проектів, а також запропоновано комбінований підхід до визначення їх набору в процесі проектування інфраструктури повоєнного розвитку. На основі матеріалів дослідження систематизовано весь процес проведення скринінгової оцінки інфраструктурних проектів з його деталізацією на етапи. Було виявлено, що адаптивний програмно-проектний підхід до стратегізації розвитку громади, на відміну від традиційного програмно-цільового планування, має характеристики та відіграє роль інноваційної технології управління територіальним розвитком.